(untitled) - Lutzer, Erwin W.; (1941-...) (U.S.A., 2012)
From panic to punchline, public perception about the return of Christ reveals an alarming lack of understanding of biblical prophecy. In The King is Coming, Pastor Erwin Lutzer lends his knowledgeable, careful handling of a topic that leaves even mature believers and students with difficult questions and unclear conclusions. For the outsiders who doubt end-times prophecy, it's a wake-up call. For those afraid that they can't ever know the answers, The King is Coming is a comfort. For anyone willing to take a serious look into the future, it is an encouraging and compelling call to action.
Keywords: Second Advent -- Biblical teaching